International relations perspectives, controversies and readings - Shimko, Keith L. 1962- (Wadsworth, Cencage Learning, 2013)
Teaching readers to think systematically and critically about international affairs, this textbook delivers brief, topical coverage with a debate framework and primary source readings included throughout